Agreement and concordance regarding reproductive intentions and contraception between husbands and wives in rural Ballabgarh, India - Yadav Kapil; Singh Bir; Goswami Kiran (Wolters Kluwer Medknow Publications, 2010)
Background: Traditionally, women have been the chief respondents in most demographic and health surveys focusing on family planning; the role of men has been limited. However, in recent years there has been realization of the importance of men′s role in family planning. Aims and Objectives: To assess the levels of agreement and concordance between husbands and wives regarding reproductive intentions and contraception. Materials and Methods: A cross-sectional survey was carried out in 200 randomly selected married couples (in the age range of 15-44 years) in village Dayalpur, Haryana. Data pertaining to reproductive intentions and contraception was collected and the level of agreement (kappa statistics) between husbands and wives was calculated. Results: The observed concordance was 67.5% for ideal family size, 84.5% for contraceptive attitude, 88.5% for fertility desire, 93.5% for unmet need, and 97% for report of number of currently living children. The adjusted kappa statistic varied from a low of 0.43 (P ≤ 0.001) (ideal family size) to a high of 0.96 ( P ≤0.001) (number of living children) with contraceptive attitude (0.7) ( P≤0.001), unmet need (0.88) ( P≤ 0.001), and current use of contraception (0.93) ( P ≤0.001) having kappa values in between. Overall, a greater degree of agreement was observed for reproductive health events as compared to family planning attitudes and intentions. An in-depth analysis of the responses in the current study provides further evidence of male domination in decision making. Conclusion: In surveys pertaining to reproductive health events, the wife′s response can be taken as proxy for the couple′s response, but for assessing family planning attitudes and intentions, there is a need to collect information from husbands and wives separately.